History, Features, Challenges and Critical Success Factors of ERP in the ERA of Industry 4.0 - Al-Amin, Md.; Hossain, Md. Tanjim; Islam, Md. Jahidul; Biwas, Sanjit (European Scientific Journal, ESJ, 2022)
This paper uses a state-of-the-art review system with a purpose to review and synthesize the latest information on the possible integration of potential disruptive technologies into the future development of ERP. Different software, such as Material Requirement Planning (MRP), Manufacturing Resource Planning (MRPII), and Computer Integrated Manufacturing (CIM) have been found to be the base of existing versions of ERP. Potential disruptive Industry 4.0 technologies that can be integrated into ERP are found to be artificial intelligence, business intelligence, internet of things, big data, blockchain technology, and omnichannel strategy. Notable Critical Success Factors of ERP are top management support, project team, IT infrastructure, communication, skilled staff, training & education, and monitoring & evaluation. Moreover, cybersecurity has been found to be the most challenging issue to overcome in future versions of ERP. This paper could help the future ERP researchers and respective stakeholders contribute to integrate newer features in the future versions of ERP.